New taxa and arrangements within the family Latrunculiidae (Demospongiae, Poecilosclerida). - Kelly, M.; Sim-Smith, C.; Stone, R.; Samaai, T.; Reiswig, H.; Austin, W. (Zootaxa, 2016)
Extensive new collections of latrunculid sponges from British Columbia, the Aleutian Islands, and the Gulf of Alaska, have extended the distributions of known species Latrunculia oparinae Samaai & Krasokhin, 2002, from the Russian Sea of Okhotsk, L. velera Lehnert et al., 2006, from the Aleutian Islands, and L. austini Samaai et al., 2006, from British Columbia. New material has facilitated detailed re-descriptions of these species and in situ images have improved our understanding of their living morphology and ecology. Several new species of Latrunculia were discovered within these collections: sympatric species Latrunculia hamanni sp. nov. and L. oparinae are described here and differentiated from each other by various field characteristics, and L. lincfreesei sp. nov. is described from the Gulf of Alaska. In terms of their higher systematics, L. austini and L. hamanni sp. nov. are recognisable within the subgenus Latrunculia du Bocage, 1869, and L. lincfreesei sp. nov. in subgenus Biannulata Samaai et al., 2006. A third subgenus, Uniannulata subgen. nov., is proposed for L. oparinae, L. velera and several fossil species in southern New Zealand and Western Australian Eocene fossiliferous sediments. In all of these species the subsidiary whorl, apical whorl, and apex of the anisodiscorhabd are fused. Living species of Uniannulata subgen. nov. are thus far restricted to the North Pacific Ocean. A new genus, Bomba gen. nov., is proposed for a rare latrunculid species, Bomba endeavourensis gen. et sp. nov., discovered in deep waters on British Columbia’s Endeavour Ridge. Finally, Latrunclava gen. nov. is proposed for species with long, sceptre-like anisoconicorhabds in addition to the typical, smaller anisodiscorhabds; Latrunclava imago gen. et sp. nov. is described from the central Aleutian Islands.